BA Projects at Linguistics for Business – at the Crossroads of PBL & PjBL - Bednarska, Katarzyna; Makowska, Aleksandra (2022)
Higher education has to respond to dynamically changing job market needs, which has become the third mission of educational institutions. Traditional methods of sharing knowledge and developing students’ skills are not satisfactory. For this reason, it is necessary to seek teaching alternatives, such as PBL (Problem-Based Learning) and PjBL (Project-Based Learning). The purpose of this paper is to present the idea of applying the above-mentioned methods to BA seminar at Linguistics for Business at University of Lodz, the innovative and interdisciplinary BA programme combining linguistics with management. The participants combine skills and knowledge gained throughout the studies, i.e. linguistics, intercultural communication, accounting and finance, or selected aspects of running a business. Moreover, creating group BA projects reflects real-life situations students can encounter at a workplace.
Keywords: PBL; PjBL; BA project; BA thesis; project charter; groupwork